Treatment of esophageal anastomotic leakage with self-expanding metal stents: analysis of risk factors for treatment failure - Persson, Saga; Rouvelas, Ioannis; Kumagai, Koshi; Song, Huan; Lindblad, Mats; Lundell, Lars; Nilsson, Magnus; Tsai, Jon A. (Endoscopy International Open, 2016)
Background and study aim: The endoscopic placement of self-expandable metallic esophageal stents (SEMS) has become the preferred primary treatment for esophageal anastomotic leakage in many institutions. The aim of this study was to investigate possible risk factors for failure of SEMS-based therapy in patients with esophageal anastomotic leakage.Patients and methods: Beginning in 2003, all patients with an esophageal leak were initially approached and assessed for temporary closure with a SEMS. Until 2014, all patients at the Karolinska University Hospital with a leak from an esophagogastric or esophagojejunal anastomosis were identified. Data regarding the characteristics of the patients and leaks and the treatment outcomes were compiled. Failure of the SEMS treatment strategy was defined as death due to the leak or a major change in management strategy. The risk factors for treatment failure were analyzed with simple and multivariable logistic regression statistics.Results: A total of 447 patients with an esophagogastric or esophagojejunal anastomosis were identified. Of these patients, 80 (18 %) had an anastomotic leak, of whom 46 (58 %) received a stent as first-line treatment. In 29 of these 46 patients, the leak healed without any major change in treatment strategy. Continuous leakage after the application of a stent, decreased physical performance preoperatively, and concomitant esophagotracheal fistula were identified as independent risk factors for failure with multivariable logistic regression analysis.Conclusion: Stent treatment for esophageal anastomotic leakage is successful in the majority of cases. Continuous leakage after initial stent insertion, decreased physical performance preoperatively, and the development of an esophagotracheal fistula decrease the probability of successful treatment.